2017
DOI: 10.1080/21645515.2016.1267082
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of iatrogenic pain between rotavirus vaccination before and after vaccine injection in 2-month-old infants

Abstract: Oral rotavirus vaccine (RV) administration in conjunction with other injectable vaccines has been used worldwide. However, whether the sequence of RV administration is associated with the reduction of injection-induced pain remains unclear.In this randomized controlled trial, we enrolled 6–12-wk-old healthy infants. The pain response of the infants was scored on the basis of their crying, irritability, facial expression, gagging and distress. A multivariate logistic regression model was used to compare the pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Studies have shown that giving something sweet like sucrose solution decrease the pain response to the injectable vaccine administration. 17,18 A study proposed that sucrose reduces pain only during the young infant period but not after 4 month of age. 19 This is because endogenous opioids are released that are activated by sweet taste and blunts pain response.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that giving something sweet like sucrose solution decrease the pain response to the injectable vaccine administration. 17,18 A study proposed that sucrose reduces pain only during the young infant period but not after 4 month of age. 19 This is because endogenous opioids are released that are activated by sweet taste and blunts pain response.…”
Section: Discussionmentioning
confidence: 99%